2021
DOI: 10.3389/fpsyg.2021.626087
|View full text |Cite
|
Sign up to set email alerts
|

Does Social Exclusion Improve Detection of Real and Fake Smiles? A Replication Study

Abstract: Research on social exclusion suggests an increased attention of excluded persons to subtle social cues. In one study (N = 32), published in Psychological Science, Bernstein et al. (2008) provided evidence for this idea by showing that participants in the social exclusion condition were better in correctly categorizing a target person’s smile as real or fake. Although highly cited, this finding has never been directly replicated. The present study aimed to fill that gap. 201 participants (79.1% female) were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although our results seem to counter previous studies examining perceptual changes following inclusion and exclusion, their findings are not consistent. While Bernstein et al (2008) found that participants were more accurate in discriminating smiles following exclusion, Schindler and Trede (2021) found no difference in participants’ ability to accurately identify smiles. Our results show yet a different pattern, with higher accuracy following inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our results seem to counter previous studies examining perceptual changes following inclusion and exclusion, their findings are not consistent. While Bernstein et al (2008) found that participants were more accurate in discriminating smiles following exclusion, Schindler and Trede (2021) found no difference in participants’ ability to accurately identify smiles. Our results show yet a different pattern, with higher accuracy following inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…We studied 6-and 7-year-olds who can distinguish between Duchenne and non-Duchenne smiles (Gosselin et al, 2002), understand and use disingenuous smiles (Kromm et al, 2014), and demonstrate sensitivity to social exclusion (Marinović & Träuble, 2018;Over & Carpenter, 2009;Song et al, 2015;Watson-Jones et al, 2016). We also tested adults because our methodology differs from that of previous adult studies (e.g., use of photos vs. videos of smiles; witnessed vs. direct inclusion/exclusion; Bernstein et al, 2008;Schindler & Trede, 2021), which provided evidence of validity for our methodology and allowed us to compare general patterns between age groups.…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
“…Yet at the same time, there is mixed evidence on how short-term, momentary vulnerabilities of social disconnection either assist or hinder social processing. For example, some research suggests that after experiencing social exclusion, individuals are better at distinguishing between Duchenne (“real”) and non-Duchenne (“fake”) smiles, and that the experience increases the cone of direct gaze [ 115 , 116 ]. Yet, other research has found that individuals are less likely to categorize faces as “happy” faces and less accurate in perceiving gaze direction after the experience of social exclusion [ 117 , 118 ].…”
Section: Discussionmentioning
confidence: 99%